2008
DOI: 10.1002/jbm.a.31717
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies of the effects of sterilization on poly(ethylene glycol) hydrogels

Abstract: The effects of several sterilization procedures on a poly(ethylene glycol) (PEG) hydrogel have been examined by electron spin resonance (ESR) spectroscopy. The crosslinked polyurethanes were synthesized by reacting PEG with a tri-functional isocyanate. The free radical concentration of unsterilized, ethylene oxide (EtO), hydrogen peroxide (H(2)O(2)), and gamma sterilized hydrogels were monitored over time. Free radical presence was observed for all the treatments, unsterilized and sterilized PEG hydrogels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A sustained release of CyA was achieved with the release lasting for ∼30 days. It was concluded that gamma sterilization was the preferred method of sterilization based on the tests conducted in this study and an earlier study conducted on PEG hydrogels 22, 23. Histological findings of gamma‐sterilized polymeric ring implants at 2 and 4 weeks demonstrate the biocompatibility of this device.…”
Section: Resultsmentioning
confidence: 51%
“…A sustained release of CyA was achieved with the release lasting for ∼30 days. It was concluded that gamma sterilization was the preferred method of sterilization based on the tests conducted in this study and an earlier study conducted on PEG hydrogels 22, 23. Histological findings of gamma‐sterilized polymeric ring implants at 2 and 4 weeks demonstrate the biocompatibility of this device.…”
Section: Resultsmentioning
confidence: 51%
“…The presence of the peroxy radical in a segmented polyurethane has been shown in other studies too 31, 33–35. The readers are also referred to a previous work that studied the evolution of free radicals over time for unsterilized and sterilized PEG‐hydrogel sheets 36…”
Section: Resultsmentioning
confidence: 58%
“…PEG is a common component of many polymer hydrogels, including drug and cell delivery systems. Sterilization methods for PEG hydrogels require consideration of potential reactions of the polyethylene backbone as well as the crosslinks . The polyether backbone of PEG hydrogels is stable to most chemical and heat sterilization methods but susceptible toward free radicals from peroxides and gamma radiation.…”
Section: Resultsmentioning
confidence: 99%